"It's the Autonomy, Stupid!" A Modest Defense of Opinion 2/13 on EU Accession to the ECHR, and the Way Forward. Issue 1 (1st March 2015) - Halberstam, Daniel
Abstract : The Court of Justice of the European Union has arrived! Gone are the days of hagiography, when in the eyes of the academy and informed observers the Court could do no wrong. The pendulum has finally swung the other way. The judicial darling, if there is one today, is Strasbourg, not Luxembourg. Not hours had passed before the Court's 258-paragraph long Opinion 2/13 on the Draft Agreement on EU Accession to the European Convention on Human Rights was condemned as "exceptionally poor." Critical voices have mounted steadily ever since, leading to nothing short of widespread "outrage."